The interaction between sleep quality and mental wellbeing in night shift workers: a case study with a qualitative approach - Mona Hastuti; Rinawati Tarigan (Journal of Midwifery and Nursing, 2023)
Night shift workers face unique challenges related to unconventional sleep patterns, which can have a significant impact on their mental well-being. In this context, this study aims to explore the impact of sleep quality on the mental well-being of night shift workers through a qualitative approach. Through an in-depth analysis of the individual experiences of 10 night shift workers with varying backgrounds, ages, genders, and work experiences, this study analyzed the challenges faced, coping strategies used, and broader implications regarding sleep quality and mental well-being. The results showed that night shift workers faced diverse challenges in maintaining sleep quality, including disrupted sleep patterns, jet lag, and work schedule uncertainty. However, these individuals adopted various coping strategies, such as maintaining a regular sleep routine, avoiding caffeine consumption in the evening, and applying relaxation techniques before bed. A supportive sleep environment, such as appropriate lighting and sleep comfort, also plays an important role in maintaining sleep quality. Implications of these findings include the need for management and organizational support in creating a work environment that supports quality sleep. This support may include stress management programs, psychological support, and schedule flexibility. In addition, this study contributes to our understanding of the interactions between sleep quality, circadian rhythms and mental well-being. The practical and academic implications of these findings may assist in the development of more effective interventions or support programs for night shift workers.